Proxy structural vector autoregressions, informational sufficiency and the role of monetary policy - Mirela S. Miescu; Haroon Mumtaz (Queen Mary University of London, School of Economics and Finance, 2019)
We show that the contemporaneous and longer horizon impulse responses estimated using small-scale Proxy structural vector autoregressions (SVARs) can be severely biased in the presence of information insufficiency. Instead, we recommend the use of a Proxy Factor Augmented VAR (FAVAR) model that remains robust in the presence of this problem. In an empirical exercise, we demonstrate that this issue has important consequences for the estimated impact of monetary policy shocks in the US. We find that the impulse responses of real activity and prices estimated using a Proxy FAVAR are substantially larger and more persistent than those suggested by a small-scale Proxy SVAR.
Keywords: C36; C38; E52; 330; information sufficiency; dynamic factor models; instrumental variables; monetary policy; structural VAR